تحليل الأخطاء الإملائية والخطية في الكتابة العربية لطلبة المدرسة الثانوية باب السلام تامبار جوكوراطا جومبانج: Analisis Kesalahan Imlak dan Khat pada Tulisan Arab Siswa Madrasah Tsanawiyah Babussalam Tambar Jogoroto Jombang - Akbar, Dhoyfun (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The difference between Arabic and pattern writing have a big effect in the students at Babussalam Tambar Jombang, and speciallyin Arabic writing. The goal of writing studies in this high school is to make the student able to write correctly, and without mistakes. But, the students do not have enough capacities and potential to realize this goal which create an obstacle and problem for them. The researcher uses in this thesis, the descriptive analyses qualitative method. It is renamed by "descriptive" because the researcher will describe the errors that was taken from Arabic writing during teaching and learning activities in the Islamic high school. It is renamed "analysis" because the errors analysis activities include the description, step by method and correction. This research has a lot of results, among them: the Arabic errors writing is related to attachment and detachment alphabet, the change of the alphabet, elimination or addition of the alphabet. The Arabic writing errors make concerned. The elimination of alphabet are more than the other errors, such as word alphabet /أ/, /ي/, then / و/, and it comes after the other errors related to change of the alphabet, such as (ن, ت, ث, ج, ز, ش, ض, غ, ك). And addition of different alphabet, for example are (أ, ب, ك, و, (ي. The other errors concern attachment and detachment alphabets are (ب ش ل). This thesis has a principal goal, which is realization and application step by step method in writing teaching, in order to solve the problem mentioned above, and amelioration of Arabic calligraphy writing in a short period.